Diversification strategy, Ownership Structure, and Firm Value: a study of public‐listed firms in Indonesia - Brahmana, Rayenda Khresna; Doddy, Setiawan; Chee, Wooi Hooy (Munich University Library, 2014)
There is a hot debate on whether internationally diversified and or industrially diversified strategy gains premium or discount on firm value. Most of the empirical studies on this topic were conducted in developed markets. However, Indonesia, as an emerging market, offers its unique characteristic in terms of ownership structure. For instance, Indonesia is dominated by family firms, but its SOEs perform better compared to family firms. This research aims to investigate the role of ownership concentration on the value of international and industrial diversification in Indonesia. We investigate how that relationship works in respect of different firm’s identity, such as different ownership level, or different owners (family, government, and foreign). We investigate the value of diversification and ownership structure of Indonesian listed firms over a panel of 2006-2010. We use robust panel regression where we report the probability values based on white robust standard errors that control for heteroscedasticity errors, as well as firm clustering, year clustering, period effect, and industry effect, which induce a within firm serial correlation error structure. To support the results, we also provide graphical evidence of the link between ownership structure, diversification strategy, and firm value. We find that ownership concentration has a prevalent and significant effect on the value of diversification. Further, we also find value discount in the industrial diversification of family firms, and value discount in the international diversification of foreign firms. Overall, our results are consistent with the conjecture that the value of diversification is adversely affected by the agency problem, suggesting that ownership concentration and firm identity play an important role in respect of the value of diversification.